Peran Badan Kepegawaian dan Perkembangan Sumber Daya Manusia terhadap Kinerja Pegawai Negeri Sipil di Aceh Barat - Ananda, Ridwan; Fitria, Syahrilzal; Sari, Cut Devi Maulida (Regress: Journal of Economics & Management, 2023)
This article aims to discuss the role of staffing agencies and human resource development on the performance of civil servants in West Aceh. The West Aceh District Personnel and Human Resources Development Agency (BKPSDM) is the government agency responsible for managing the staffing, education and training sectors in West Aceh District. To achieve the desired performance, employees must receive training in accordance with their duties so that they can carry out their duties in a professional manner. Education and training are important factors in forming professional human resources. In an organization, it is necessary to involve employees in training activities that are expected to improve employee performance and productivity. In this article the method used is qualitative analysis, where the research results are more oriented towards describing and describing information obtained through interviews and observation.